Aeromobilities' extra-sectoral costs: a methodological reorientation. Issue 4 (3rd July 2020) - Lin, Weiqiang; Harris, Tina
ABSTRACT: For over a decade, scholars have graced a number of aeromobilities' socio-cultural dimensions, from being in an airport to commanding an aeroplane. Yet, while this work has heightened appreciations of the political nature of aerial worlds, the propensity has been to focus on the immediate arrangements and politics related to flight. Using civil aviation as an example, this article offers a methodological reorientation and conceptual rethink of how aeromobilities' (re)production invokes far-reaching political economies in excess of the core activity of aerial conveyances. It seeks to open up worldly webs of iniquitous movements and relations that make aerial life – rather than flying per se – possible in the first place. Interspersing a selection of our research with extant literature, reports and statistics, the article outlines, in coincidence with our earlier findings, two ways in which civil aviation has thus incurred extensive extra-sectoral costs: the material mobilisation of resources for air infrastructures, and the mobilisation of populations and labour for aeromobile development. The discussion aims ultimately to promote a more nuanced understanding of the constituents, and costs, of moving in the present age.